Combating Drug Abuse through Rehabilitation for Foreign Nationals with the SMART Method (Self-Management and Recovery Training) at the Drug Rehabilitation Foundation in Denpasar City - Subawa, Ida Bagus Gede; Sutrisni, Ni Komang; Lis Julianti (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
Drug abuse is a serious problem faced by many countries, including Indonesia. To overcome this problem, the Indonesian government provides rehabilitation sanctions for drug users, including foreign citizens living in Indonesia. This research aims to analyze the regulation of drug rehabilitation for foreign nationals in criminal acts of drug abuse in Denpasar City and this research also highlights the importance of the Self Management and Recovery Training (SMART) method as an effective solution in the rehabilitation of foreign nationals caught in drug abuse in Indonesia. The research method used is empirical legal research with a critical qualitative approach. The data collection technique was carried out by interviews where informants were selected purposively. Data processing analysis techniques are carried out in a qualitative descriptive manner. The research results show that foreign citizens involved in drug abuse crimes in Denpasar City can undergo the same rehabilitation program as Indonesian citizens. This process begins with applying to local authorities, such as the police or authorized agencies. However, rehabilitation policies for foreign nationals depend on various factors, including the severity of the offense and whether they are willing to cooperate with authorities, and drug rehabilitation for foreign nationals is important. The SMART method is an effective rehabilitation method for foreign nationals because this program can be adapted to different individual needs, languages, and cultures. This program also emphasizes individual responsibility in the recovery process, so that it can help individuals to build a better sense of self-confidence and self-control.